2017
DOI: 10.1149/2.1471712jes
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Sulfonated Phenylene Poly(Arylene Ether Ketone) Semiblock Copolymer Membrane in Wet-Dry Cycling for PEFCs

Abstract: The mechanical durability of sulfonated poly (phenylene) (SPP) membrane, used for polymer electrolyte fuel cells (PEFCs), is evaluated by the United States Department of Energy (USDOE) stress protocol involving wet-dry cycling, and the degradation is analyzed specifically by comparing with sulfonated poly(arylene ether ketone) (SPK) membrane. Initially, the SPP membrane exhibits 2-fold higher stiffness and 50% lower dimensional change ratio than the SPK membrane. In durability cycling, the SPP membrane lasts m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In the post-test SPK membrane, a macroscopic crack through the cathode, membrane, and anode was observed at the edge of the electrode region both in the photographic (Figure S2a) and in the cross-sectional SEM (Figure a) images. The reason why the macroscopic crack was observed only at this region is the stress concentration, which was well-described in the literature. , In contrast, in the post-test NF-reinforced SPK membrane, a macroscopic crack was not observed in the photographic image (Figure S3). In the cross-sectional SEM images (Figure c and d), no crack of any size was detected.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In the post-test SPK membrane, a macroscopic crack through the cathode, membrane, and anode was observed at the edge of the electrode region both in the photographic (Figure S2a) and in the cross-sectional SEM (Figure a) images. The reason why the macroscopic crack was observed only at this region is the stress concentration, which was well-described in the literature. , In contrast, in the post-test NF-reinforced SPK membrane, a macroscopic crack was not observed in the photographic image (Figure S3). In the cross-sectional SEM images (Figure c and d), no crack of any size was detected.…”
Section: Resultssupporting
confidence: 64%
“…Consequently, the wet−dry cycle number (N) of the NF-reinforced SPK cell was 18 320, which was more than 60 times higher than that of the SPK cell (N = 300) with similar cell configuration but slightly different tested conditions (the United States Department of Energy (USDOE) protocol) reported in the literature. 24,25 Thus, quantitative comparison between two cells should be avoided; however, the NF-reinforced SPK cell possessed much higher mechanical durability than the parent SPK membrane without the use of extra components such as a subgasket film and/or soft gas diffusion layer. 24,25 As a reference, it was reported that the Nafion XL membrane, reinforced by a microporous PTFE-rich mechanical support layer, survived in a similar humidity cycling test for 20 000 cycles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been reported that hydrocarbon ionomer membranes exhibited lower wet-dry cycle durability than those for PFSA membranes ( 32 ), mainly due to the lower dimensional stability (or higher water absorbability) of hydrocarbon ionomer membranes. Thus, the wet-dry cycle durability of the SPP-QP membrane was evaluated by means of the U.S. Department of Energy (DOE) protocol ( 33 , 34 ). As a preliminary result, the SPP-QP membrane lasted more than 6000 wet-dry cycles without mechanical failure (without increase in gas permeability).…”
Section: Resultsmentioning
confidence: 99%
“…The wet-dry cycle durability was evaluated by the DOE protocol. Details on the evaluation conditions were described in our previous paper ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, aromatic ionomers with high IECs generally show high water uptake and swelling and thus, suffer from mechanical failure in practical fuel cells, in particular, when the humidity changes frequently ( Ishikawa et al., 2017 ). One of the effective approaches is to reinforce the aromatic ionomers with mechanically robust, non-ionic porous substrate.…”
Section: Introductionmentioning
confidence: 99%